2009
DOI: 10.1387/ijdb.072517lo
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest ontogeny during secondary neurulation: a gene expression pattern study in the chick embryo

Abstract: In the prospective lumbo-sacral region of the chick embryo, neurulation is achieved by cavitation of the medullary cord, a process called secondary neurulation. Neural crest cells (NCC) are generated in this region and they give rise to the same types of derivatives as in more rostral parts of the trunk where neurulation occurs by dorsal fusion of the neural plate borders (primary neurulation). However, no molecular data were available concerning the different steps of their ontogeny. We thus performed a detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…All of these characteristics of NCC generation have been described principally in regions of primary neurulation. We recently showed that the same events occur more caudally in regions belonging to secondary neurulation (Osorio et al, 2009).…”
Section: Introductionmentioning
confidence: 85%
“…All of these characteristics of NCC generation have been described principally in regions of primary neurulation. We recently showed that the same events occur more caudally in regions belonging to secondary neurulation (Osorio et al, 2009).…”
Section: Introductionmentioning
confidence: 85%
“…Intriguingly, a very similar kinetics of NC cell delamination has been described for the zebrafish trunk or for regions of secondary neurulation in amniotes, even though they differ in their neurulation processes. 53,64 In conclusion, while the cellular events accompanying NC cell formation and delamination are likely to be influenced by the mode of neurulation (i.e., primary vs. secondary), the timing when delamination occurs seems defined by rules independent of neurulation (i.e., cranial vs. truncal/somitic), thus raising the possibility that the regulatory events triggering EMT may be governed by processes independent of the mode of neurulation and conserved among vertebrates.…”
Section: The Neural Crest a Cell Population Issued By An Emtmentioning
confidence: 99%
“…At levels posterior to the otic placode, i.e., at somitic levels, including in regions of secondary neurulation, NC cell migration starts well after neural tube closure and ectoderm healing, and this is true for all amphibian and amniote species studied so far. 29,53 The consequence of the different time lags between NC cell delamination and neural tube closure in the head and trunk is that the relative spatial positioning of the NC, ectodermal and neural tube populations, their organizations and mutual interactions, as well as their states of differentiation are different. At cranial levels and particularly in the chick midbrain (Fig.…”
Section: The Neural Crest a Cell Population Issued By An Emtmentioning
confidence: 99%
“…This happens possibly to enable free migration of neural crest cells. Changes in the amount of laminin with time have been shown to affect cell differentiation (11) . Sometimes the lumen has been observed to develop even from a cavity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that laminin is present in mesenchymalepithelial transition zones throughout HH-18 and 20 stages and that it provides polarization of cells there and contributed to the development of the basement membrane. This environment with these cells produces secondary neurulation (11) . However, exact effect of laminin in this period is yet to be established.…”
Section: Introductionmentioning
confidence: 99%